On-Campus Student Medical Centre Between Theory and Practice Qassim University student medical centre - Case Study - Mohamed, Sherif Elsayed Elsaid; Elzainy, Ahmed; Rasheed, Zafar; Alothaim, Yunes; Alsughayer, Hasan HH.; Alamer, Hamad; Alnassar, Mohammed A.; Alharbi, Fawaz Saad; Alharbi, Mousa Abdullah; Alharbi, Ahmed Mohammed; Al-Harbi, Waleed Dakhel; Abdulmonem, Waleed Al (Journal of Sustainability Perspectives, 2025)
Providing comprehensive health care to students on campus is crucial to enhancing their overall well-being and academic success, as medical health care for students on Qassim University campus aims to meet their diverse health needs. Qassim University has established an integrated medical city that aims to provide health care services to students and employees within the university campus. The city’s facilities are designed to deal with the medical needs of students effectively and comfortably. This research highlights the key aspects and benefits of on-campus medical health care, including its role in maintaining physical and mental health, enhancing both students' academic performance, and a supportive campus environment. Qassim University offers wide-ranging free health services to all students, as these services are provided through the Medical City Center, which includes an integrated team of employees, doctors, nurses, technicians, and health care specialists, who can manage chronic disorders, provide preventive care, and diagnose and treat diseases. Common. The paper also highlights the various medical services that the university provides to its employees, such as primary health care that takes place in specialized outpatient clinics, as well as urgent care that requires immediate attention, as well as surgical interventions to treat various medical conditions, in addition to immunization services and providing vaccinations against a wide range of diseases. the range. Also disseminating and supporting students’ mental health through a group of expert psychologists who can provide counseling services to university students. On the other hand, Qassim University offers health promotion initiatives that aim to raise awareness on various health topics. These initiatives include campaigns, workshops, seminars, and events to educate students and maintain their health, and other medical services that will be discussed in detail during the research.